The Sociolinguistic Perspective in Abu AL- Brakat AL Anbary of Linguistic Analysis in his Book "Asrar AL Arabia" (Islamic Sciences Journal, 2023)
This paper seeks to clarify the role of Ibn al-Anbari in Syntactical analysis, by monitoring the sporadic references and hates in his book Asrar al-Arabiyya, which refer to Ibn al-Anbari's alertness and attention to the social aspect of the method of syntactical analysis, in light of sociolinguistics.This research has answered the following question: Did Ibn Al-Anbari pay attention to the social dimension in setting the criteria for the syntactical system?The importance of the research lies in its contribution to reviving one of the origins of the linguistic lesson among Arab grammarians through the work of Ibn Al-Anbari in the secrets of Arabic in particular.
Keywords: Sociolinguistics, Abu Al-Barakat, the semantic note, the culture of society, the context.